Prenatal Yoga Untuk Kondisi Kesehatan Ibu Hamil - Kadek Dwitya Widi Adnyani (Jurnal Yoga dan Kesehatan, 2021)
In essence, pregnancy is a natural nature that must be carried out by women which at the same time can be a threat to the safety of their souls. So that this is not a serious threat, pregnancy needs treatment with good help. One of the activities that pregnant women can do is doing prenatal yoga activities. Yoga is a form of mind body practice that originated in India. Yoga is a science that explains the link between physical, mental, and spiritual humans to achieve overall health. Prenatal yoga (yoga for pregnancy) is a modification of classical yoga which has been adapted to the physical condition of pregnant women which is done with a more gentle and slow intensity. The principles of prenatal yoga are the principles of prenatal yoga, namely breathing with full awareness. Prenatal yoga practice can help improve the health of pregnant women. Posture and breathing exercises have a relaxing effect and help reduce physical stress. There are several techniques that can be done in prenatal yoga, namely calming or centering the mind, pranayama, warming up and implementing asanas for pregnant women.